Ms.: STUDI EFEKTIVITAS LARVA BLACK SOLDIER FLY (BSF) SEBAGAI AGEN BIOKOKNVERSI SAMPAH ORGANIK: STUDI KASUS DI PASAR TRADISIONAL TANJUNG - safitri, Rizkiida; Husnayati Hartini; Dwi Rahayu Susanti (Jurnal Teknologi Lingkungan, 2025)
Organic waste is one of the main problems in traditional markets due to its abundant quantity and potential to cause unpleasant odors and environmental pollution if not properly managed. The utilization of Black Soldier Fly (BSF) larvae as a bioconversion agent is one environmentally friendly and economically valuable management alternative. This study aims to determine the effectiveness of BSF larvae in degrading three types of organic waste from Tanjung Traditional Market, namely vegetables, fruits, and fish waste. Each treatment used 200 g of BSF larvae with a total of 6 kg of organic waste provided gradually over six days. The observed parameters included initial and final waste weight, larval weight gain, feed consumption, pH, temperature, Waste Reduction Index (WRI), and Efficiency of Conversion of Digested food (ECD). The results showed that BSF larvae were able to degrade all three types of organic waste with varying effectiveness. The highest WRI value was obtained from fish waste at 426.7 g/day, followed by fruit waste at 366.7 g/day, and vegetable waste at 325 g/day. Larval weight gain and ECD values were also highest in fish waste, indicating a more optimal nutrient conversion efficiency compared to fruits and vegetables. The higher degradation rate in fish waste was influenced by its protein and fat content, which are easier to decompose, while crude fiber in vegetables slowed down the degradation process. Based on these results, BSF larvae proved to be effective as a bioconversion agent for organic waste, particularly fish waste, thus offering potential as an alternative solution for environmentally friendly market waste management, reducing pollution, and providing additional economic value.